ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI LAMA SAKIT DIARE PADA ANAK DI DESA RANTE WRINGIN KECAMATAN BULUSPESANTREN KABUPATEN KEBUMEN TAHUN 2012 - Deni Setyowati; Cokro Aminoto; Nurlaila Nurlaila (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2013)
Diarrhea still becomes a major cause of morbidity and mortality. In developing countries many children are suffering from diarrhoea for more than 12 times a year and it becomes the cause of death with CRF 15% to 34% of all deaths and the highest incidence occurs in children. Diarrhoea disease is one of the environmentally-based diseases. The two dominant factors causing the disease are water supply and excreta disposal. Both of these factors will interact with human behavior. This study aims to know the factors influencing the length of Diarrhea illness in Rante Wringin Village Buluspesantren, Kebumen in 2012. This study used cross-sectional correlation approach. The data were analyzed using frequency distributions and bivariate analysis using chi square test statistic and logistic regression. The results showed no correlation between places to defecate with diarrhoea with p: 0.038 and no correlation between clean water usage with the length of diarrhoea illness with p: 2.057. There was a correlation between the knowledge level of the parents with the length of diarrhoea illness with p: 0.018. There was no correlation between nutritional status with the length of diarrhoea illness with p: 1.000. There was no correlation between economic status with the length of diarrhoea illness with p: 0.03. Keywords: a place to defecate, children, economic status the use of clean water, knowledge, nutritional status, , the length of diarrhoea illness